The Moderating Impact of Employee Job Satisfaction on the Service Quality–Customer Satisfaction Relationship: The Case of the Lebanese Healthcare Institutions - Johnny Chaanine; Esther B. Sleilati (SAGE Open)
In an era where managers are seeking to improve customer satisfaction and decrease customer response time, healthcare organizations are striving to increase patient satisfaction by improving communication channels, eliminating errors, and reducing patient waiting time. Job satisfaction plays a significant role in determining service quality and in providing high-quality service to customers. This study focuses on the importance of job satisfaction as a moderator of the service quality-customer satisfaction relationship in the Lebanese healthcare context. The importance of investigating this relationship lies in the fact that Lebanon has a service-based economy; thus, improving the service quality of this sector can significantly impact the country’s overall deteriorating economic performance. This can help to develop effective strategies to improve employee morale and customer/patient satisfaction despite poor financial and living conditions, while providing valuable insights to enhance the working conditions in a vital sector, ultimately leading to the economic growth of a country collapsing in an unprecedented manner. Despite the significance of service quality from the customer and employee standpoints in service quality literature, few studies have combined these three perspectives. A quantitative study was conducted with 1,128 healthcare providers confirming that the higher the job satisfaction, the higher the quality of the offered services, and the higher the customer/patient satisfaction even if job satisfaction had been slightly improved. This study is equally an eye opener for healthcare managers to motivate employees and boost their satisfaction despite a collapsing economy and degenerating living and health conditions.